2017
DOI: 10.1007/s00068-017-0865-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PECARN and CATCH clinical decision rules in children with minor blunt head trauma

Abstract: While both PECARN and CATCH were found to be effective in determining the necessity of CBT for children with minor blunt head trauma, PECARN proved to be more useful for emergency services because of its higher sensitivity. The authors suggest that conducting a CBT scan based on clinical decision rules may be a suitable approach for early detection of the presence of intracranial acute pathologies in young children with minor blunt head trauma, especially if the GCS score is < 15 and non-frontal hematomas are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In a study in the literature, 94% of the patients were discharged from the pediatric emergency service. [3] In our study, 90% of the patients were monitored up to about 8 hours, and 97% of them weredischarged from thepediatricemergency service. We can explain one of the reasons for our high CT rate to be the shortness of our monitoring period.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In a study in the literature, 94% of the patients were discharged from the pediatric emergency service. [3] In our study, 90% of the patients were monitored up to about 8 hours, and 97% of them weredischarged from thepediatricemergency service. We can explain one of the reasons for our high CT rate to be the shortness of our monitoring period.…”
Section: Discussionmentioning
confidence: 72%
“…It is also important to determine patients requiring CT because of the risk of cancer due to radiation. [3] Clinical decision rules help physicians for the decision ofthe requirement of a CT scan in patients with minor head trauma. Of these rules, the most frequently used is the USA based PECARN (The Pediatric Emergency Care Applied Research Network), while the England based CHALICE (The children's head injury algorithm for the prediction of important clinical eventsrule) and Canada based CATCH(Canadian Assessment of Tomography for Childhood Head injury rule) are other frequently used clinical decision rules.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, GCS is frequently used in separating the patients with head trauma into subgroups, diagnosis and treatment methods, and repetitive evaluation of patients. [15] It was reported in many previous studies that low GCS values and changes in consciousness are related to mortality due to brain damage and head trauma. [16][17][18] In addition, GCS and changes in consciousness are common physical examination findings that indicate a high risk in PECARN, CATCH, and CHALICE which are the most frequently used decision-making rules for MHTs in children.…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of the same study, the positive predicted value was 19%, while the negative predicted value was 95%. 22 Lorton et al found among children under the age of 2 years that PECARN had a sensitivity of 100%, specificity of 64%, positive predicted value of 2%, and negative predicted value of 100%, while these values were, respectively, 100%, 72%, 2%, and 100% for children at the age of 2 years or older. For all cases, the sensitivity value was calculated as 100%, specificity was 70%, positive predicted value was 2%, and negative predicted value was 100%.…”
Section: Discussionmentioning
confidence: 98%